(untitled) (Minerva. Revista de Filología Clásica, 2019)
Reseña de Guy Halsall, ed., Humour, History and Politics in Late Antiquity and the Early Middle Ages, Cambridge, 2002, 208 pp. ISBN 0 521 81116 3